THE IMPORTANCE OF HUMAN RESOURCE POTENTIAL IN MANUFACTURING ENTERPRISES UNDER CONDITIONS OF DIGITAL TRANSFORMATION - Sharopov, Temirmalik (THE INNOVATION ECONOMY, 2026)
The current thesis examines the significance of human resource potential for manufacturing companies amid digitalization. Along with growing productivity, which follows from the implementation of digitalization, the value of well-educated specialists who are digitally literate rises. In accordance with research data, the significant human resource potential plays a crucial role in the efficient use of digitalization tools and innovation, and the successful functioning of enterprises.